Preliminary results of vein wrapping for treating hyperaesthesia of the superficial sensory radian nerve - Nur Azree Ferdaus, Kamudin; Amir Adham, Ahmad; Ahmad Suparno, Bahar; Shalimar, Abdullah (2019)
Objectives / Interrogation: Hyperaesthesia of superficial sensory of radial nerve following decompression of de Quervain tenosynovitis is relatively common. The oversensitive pain is described as a sharp-slicing pain located over the radial aspect of the dorsum of wrist till the base of the thumb. The pain occurs continuously even at rest. Although in most cases, hyperaesthesia is successfully treated with opioids, adjuvant medication (antidepressant, anticonvulsant, baclofen or topical local analgesia) and physiotherapy (transcutaneous-electro-nerve-stimulator and desensitization), some authors propose for surgical procedures (adhesiolysis, neurolysis, vein wrapping). A few authors reported success in threating hyperaesthesia for median nerves. However, to our knowledge, there is no case report of vein wrapping in treating hyperaesthesia of the superficial sensory of the radial nerve. Methods: We report vein wrapping in treating hyperaesthesia of the superficial sensory of radial nerve following surgery for de Quervain. An 80-year-old male with chronic left wrist pain was diagnosed with de Quervain tenosynovitis and underwent surgical decompression of the first extensor compartment. The pain of this left wrist did not resolve more than a year despite regular physiotherapy and medication. The pain was described as a "sharp" pain even on slight touch at the dorsal radial aspect the wrist with the pain score of 8. There was no weakness of wrist, fingers or thumb in extension. Results and Conclusions: Using the same incision from previous surgery, the superficial sensory of radial nerve was identified and we noticed the nerve was covered with previous fibrous tissue. It was pale, irregular and swollen. There was no neuroma of the nerve. We harvested the dorsal vein of the wrist, 6 cm in length, and wrapped it cylindrically around the affected nerve. Immediately on day 1 postoperative, the sharp pain of wrist reduced from 9 to 5. We assessed the pain score in the clinic in 2 weeks, 4 weeks and 6 weeks. The pain score was decreasing on each occasion. The patient was satisfied and improved in his wrist motion.